THE EFFECTIVENESS OF PROBLEM BASED LEARNING AND SCIENTIFIC LEARNING MODEL COMBINED WITH COOPERATIVE JIGSAW IN MATHEMATICS LEARNING FOR STUDENTS’ ACHIEVEMENT AND MATHEMATICAL COMMUNICATION SKILL - Vety Triyana Kurniasari , Heri Retnawati (Jurnal Pedagogi Matematika, 2018)
Abstract The aim of this study was to know about the effect of Problem Based Learning (PBL) and learning with scientific approach combined with cooperative learning Jigsaw in terms of mathematical communication skill and student’s achievement in mathematic. The research method is quasi experiment which used pretest posttest group design. The data were collected through a mathematical communication and student’s achievement andobservation form for learning activities. The result of this study showed that PBL-Jigsaw is not effective in mathematical student’s achievement and student’s mathematical communication skill. While, scientific approach-Jigsaw is effective in mathematical student’s achievement and student’s mathematical communication skill. PBL-Jigsaw is not better than scientific approach-Jigsaw in mathematical student’s achievement and student’s mathematical communication skill reviewed by gain score of posttest and pretest students. Keyword: PBL, cooperative Jigsaw, scientific approach, mathematical communication, mathematical student’s achievement